2017
DOI: 10.3892/etm.2017.4608
|View full text |Cite|
|
Sign up to set email alerts
|

miR-663b promotes tumor cell proliferation, migration and invasion in nasopharyngeal carcinoma through targeting TUSC2

Abstract: The authors' previous study revealed that the serum levels of microRNA (miR)-663b are significantly increased in patients with nasopharyngeal carcinoma (NPC), and are associated with NPC progression and poor prognosis. However, the molecular mechanism of underlying NPC growth and metastasis remains unclear. In the present study, quantitative polymerase chain reaction and western blot analyses were performed to examine changes to mRNA and protein expression, respectively. MTT, wound healing and Transwell assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Accumulating evidence indicates that the dysregulation of miRNAs is involved in various types of diseases (23,24). The abnormal expression of miR-663b has been observed in a variety of malignancies: Shu et al (25) demonstrated that the knockdown of miR-663b inhibited cell proliferation and promoted apoptosis in osteosarcoma by regulating tumor (26) identified that miR-497 and miR-663b levels in the plasma may be novel biomarkers for bladder cancer; Cai et al (27) suggested that the epigenetic inhibition of miR-663b by HOTAIR promotes cell proliferation in pancreatic cancer by upregulating insulin-like growth factor 2; Wang et al (28) reported that miR-663b promotes cell proliferation and epithelial-to-mesenchymal transition by directly targeting SMAD7 in nasopharyngeal carcinoma; Wang et al (29) demonstrated that pterostilbene dose-dependently inhibited cell proliferation in human endometrial cancer by downregulating miR-663b, and BCL2L14 was verified as a direct target of miR-663b; Liang et al (30) revealed that miR-663b promotes migration and invasion of nasopharyngeal carcinoma cells through downregulating TUSC2; and, using a miRNA microarray analysis, Pellatt et al (15) recently demonstrated that miR-663b is upregulated in CRC tissues compared with normal mucosa. However, the mechanism of action of miR-663b in CRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that the dysregulation of miRNAs is involved in various types of diseases (23,24). The abnormal expression of miR-663b has been observed in a variety of malignancies: Shu et al (25) demonstrated that the knockdown of miR-663b inhibited cell proliferation and promoted apoptosis in osteosarcoma by regulating tumor (26) identified that miR-497 and miR-663b levels in the plasma may be novel biomarkers for bladder cancer; Cai et al (27) suggested that the epigenetic inhibition of miR-663b by HOTAIR promotes cell proliferation in pancreatic cancer by upregulating insulin-like growth factor 2; Wang et al (28) reported that miR-663b promotes cell proliferation and epithelial-to-mesenchymal transition by directly targeting SMAD7 in nasopharyngeal carcinoma; Wang et al (29) demonstrated that pterostilbene dose-dependently inhibited cell proliferation in human endometrial cancer by downregulating miR-663b, and BCL2L14 was verified as a direct target of miR-663b; Liang et al (30) revealed that miR-663b promotes migration and invasion of nasopharyngeal carcinoma cells through downregulating TUSC2; and, using a miRNA microarray analysis, Pellatt et al (15) recently demonstrated that miR-663b is upregulated in CRC tissues compared with normal mucosa. However, the mechanism of action of miR-663b in CRC remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that exosomal miR‐663b promoted cell proliferation and the EMT in BC cells, implying it functioned as tumor promoter in BC. Interestingly, miR‐663 are also involved in cancer process with pro‐ or anti‐tumor functions (Zang et al, ; Liang et al, ). Whether there is a relationship between miR‐663 and miR‐663b is worth further studies.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐663b has been found to be elevated in plasma from patients with BC and was identified as a potential circulating biomarker for clinical detection of BC (Du et al, ). It has been reported that miR‐663b promotes tumor cell proliferation and the epithelial–mesenchymal transition (EMT) in nasopharyngeal carcinoma (Liang et al, ; Wang et al, ) and osteosarcoma (Shu et al, ). However, whether it exists in the exosomes and the functional roles of exosomal miR‐663b in BC processes have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic activities of miR-93, miR-98 and miR-197 in lung cancer are mediated by the silencing of TUSC2 [33]. In ovarian and nasopharyngeal cancers it has been reported that miRNA-663 promotes cell growth, migration and invasion by inhibiting TUSC2 [34,35].…”
Section: Discussionmentioning
confidence: 99%